Factors leading to absenteeism among workers in district and land offices of Jerantut and Temerloh / Suryati Zainudin, Nurul Hana Apeloh and Faizatul Hanim Abdullah - Zainudin, Suryati; Apeloh, Nurul Hana; Abdullah, Faizatul Hanim (2008)
The purpose of the study was to determine the factor of absenteeism in District and Land Office in Jerantut and Temerloh. This research focused on the main problems which cause absenteeism such as health, work environment and job satisfaction, and financial. The method that we used to conduct this research was questionnaires. These questionnaires had been distributed randomly among the workers in District and Land Office using simple random sampling. The number of respondents who answered these questionnaires was 52. After data amalysis, the main factor that caused absenteeism among workers in District and Land Office in Jerantut and Temerloh was health. There were several types of health problems stated as chronic diseases such as heart problem, diabetis, asthma, cancer and high blood pressure. Besides that, the second factor that leads to absenteeism was financial problem. In order to decrease absenteeism in this organization, the top management should overcome this problem such as develop an Attendance Policy Program and suggestion for future research.